Characterisation of antioxidants in photosynthetic and non‐photosynthetic leaf tissues of variegated Pelargonium zonale plants. (3rd February 2016) - Vidović, M.; Morina, F.; Milić‐Komić, S.; Vuleta, A.; Zechmann, B.; Prokić, Lj.; Veljović Jovanović, S.
Abstract: Hydrogen peroxide is an important signalling molecule, involved in regulation of numerous metabolic processes in plants. The most important sources of H2 O2 in photosynthetically active cells are chloroplasts and peroxisomes. Here we employed variegated Pelargonium zonale to characterise and compare enzymatic and non‐enzymatic components of the antioxidative system in autotrophic and heterotrophic leaf tissues at (sub)cellular level under optimal growth conditions. The results revealed that both leaf tissues had specific strategies to regulate H2 O2 levels. In photosynthetic cells, the redox regulatory system was based on ascorbate, and on the activities of thylakoid‐bound ascorbate peroxidase (tAPX) and catalase. In this leaf tissue, ascorbate was predominantly localised in the nucleus, peroxisomes, plastids and mitochondria. On the other hand, non‐photosynthetic cells contained higher glutathione content, mostly located in mitochondria. The enzymatic antioxidative system in non‐photosynthetic cells relied on the ascorbate–glutathione cycle and both Mn and Cu/Zn superoxide dismutase. Interestingly, higher content of ascorbate and glutathione, and higher activities of APX in the cytosol of non‐photosynthetic leaf cells compared to the photosynthetic ones, suggest the importance of this compartment in H2 O2 regulation. Together, these results imply different regulation of processes linked with H2 O2 signalling at subcellular level. Thus, we propose green‐white variegated leaves as an excellent system for examination of redox signal transduction and redox communication between two cell types, autotrophic and heterotrophic, within the same organ.